APPLICATION OF DIET MANAGEMENT (LITTLE BUT OFTEN) IN NORMAL BLOOD SUGAR STABILITY IN DIABETES MELLITUS PATIENTS - Mukhammad Toha; Mokh Sujarwadi; Ida Zuhroidah (UNEJ e-Proceeding, 2023)
Background: The failure to control blood sugar levels in people with diabetes mellitus is due to the inability to control hunger. The frequency of eating that is more than normal is often experienced by people with diabetes mellitus due to frequent hunger. An inadequate supply of glucose into cells responds to the brain to increase the activity of the digestive organs. The collection of glucose into cells is influenced by the adequacy of the insulin hormone produced by the pancreas and the ability of insulin receptors in cells to recognize insulin hormones. This study aims to identify the effects of dietary management (small but often) on controlling blood sugar in diabetes mellitus patients. Methods: This study used a pre-experimental design with a one-group pre-test post-test approach. The independent variable is dietary management (a little but often), and the dependent variable is blood sugar levels. The population in this study were people with diabetes mellitus in the Rembang area using a purposive sampling technique. The number of samples is 40 people; the research time is two months. Data collection instruments were a glucose test, a calorie counter, and a control card. Data analysis used paired t-test. Results: There is a significant effect of dietary management (a little but often) on blood sugar stability with a significance level of p=0.000. Setting a realistic diet in people with diabetes mellitus helps reduce blood sugar levels. Calculating the number of calories needed each day and then dividing them according to the wishes of people with diabetes mellitus without changing eating habits and the number of calories required can provide comfort to reduce stress. Conclusions: Dietary management (little but often) positively affects blood sugar stability. The freedom to determine the meal schedule is a diabetic's choice and can increase discipline and responsibility in complying with it.